计算:⑴√6×(√2+√6)⑵(2√3-1)²⑶(2√3+3√2)(2√3-3√2)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/09 08:47:04
计算:⑴√6×(√2+√6)⑵(2√3-1)²⑶(2√3+3√2)(2√3-3√2)计算:⑴√6×(√2+√6)⑵(2√3-1)²⑶(2√3+3√2)(2√3-3√2)计算:⑴√6
计算:⑴√6×(√2+√6)⑵(2√3-1)²⑶(2√3+3√2)(2√3-3√2)
计算:⑴√6×(√2+√6)⑵(2√3-1)²⑶(2√3+3√2)(2√3-3√2)
计算:⑴√6×(√2+√6)⑵(2√3-1)²⑶(2√3+3√2)(2√3-3√2)
⑴√6×(√2+√6)
=2√3+6;
⑵(2√3-1)²
=12+1-4√3
=13-4√3;
⑶(2√3+3√2)(2√3-3√2)
=12-18
=-6;
计算(2√2-3√6)÷√2+√27;求计算方式
1+2-3-4+5+6-7-8+.+2001+2002-2003-2004+2005+2006计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~
计算:√6÷(3√2×√12)
根数计算:√6-√2
数学计算/√3-2/
计算(√3+√2)²
如何计算(√4/3-2√3)*(-√6)
计算 ( 2√48-3√27) ÷ √6
(√5+6)(3-√5) 计算
计算2√27×3√6 谢谢了😜计算2√27×3√6谢谢了😜
计算:(-3√2)*(-√2)^7
计算√48/2√3
计算:2√12+3√48
计算√27-√3/2
计算√3(√2-√3)-√24-|√6-3|
计算√2(√2+√6)-√27=?
计算√2(√2+√6)-√27=?
计算√32×1/2